A Case Report of Tongue Edema due to Laryngeal Mask with Introducer - Hayrettin DAŞKAYA; Taner ÇİFTÇİ; Kadir İDİN; Kürşat GÜL; Ufuk TOPUZ; Hakkı ÖLÇÜLÜ (Bezmiâlem Science, 2018)

(untitled)
Airway management using a laryngeal mask is an especially preferred noninvasive technique because of its achievement of hemodynamic stability and ease of application in surgeries that have short surgery time and do not require specific positions such as the prone position. Although it is easily performed, serious complications may manifest rarely because of lack of experience and inappropriate choice of instrumentation. In this case report, clinical management and treatment options of tongue edema that developed because of the forgotten introducer in laryngeal mask application are presented.